Association of rs1738074 polymorphism of TAGAP gene with susceptibility to multiple sclerosis in the Iranian population. (1st May 2017) - Jazaeri, Ali; Vallian, Sadeq
Highlights: TAGAP rs1738074 single nucleotide polymorphism is associated with the prevalence of multiple sclerosis in the Iranian population. The T/T genotype of rs1738074 shows a suppressor effect on the prevalence of multiple sclerosis in the Iranian population. The rs1738074 can be further studied as a possible risk factor in the incidence and prevalence of MS. Abstract: Multiple sclerosis (MS) is one of the most common diseases of the central nervous system (CNS) in the Iranian population. To date, association of many genes with the prevalence and progression of the disease have been investigated. In the present study, the impact of rs1738074 single nucleotide polymorphism (SNP) in the TAGAP gene ( TAGAP rs1738074) on the risk of MS was evaluated in a sample of the Iranian population. In a case control study, genotyping was performed on 300 patients and normal individuals. The data were analyzed using Pearson's chi-square test. The results showed a significant difference in the SNP frequency between case and control groups (p-value = 0.049). The genotype frequencies of TT, TC and CC in patients were 10.67%, 51.33% and 38%, respectively, and in normal individuals were 20.66%, 42.67% and 36.67%, respectively. The results showed a significant difference in the genotype frequency of T/T between the patient and control groups (p < 0.05). Interestingly, individuals with T/T genotype were estimated to be less susceptible to MS ((p-value = 0.025), Fisher's exact test), odd ratio was 2.18 (controls versus MS patients) with 95% CI: 1.137–4.187. The results suggested that TAGAP rs1738074 polymorphism could be considered as a risk factor in the prevalence of MS in the Iranian population.